Sweet corn induced shading reduces groundnut yield and alters dry matter partitioning in a durian-based intercropping system - Mohd Hizwan Ajud; Borhan Abdul Haya; Sharif Azmi Abdurahman; Azwan Awang; Mohamadu Boyie Jalloh; Chin, Clament Fui Seung; Siti Suliza Salamat; Januarius Gobilik; Salumiah Mijin (UniSE Press, 2025)
Intercropping of sweet corn and groundnut is often practiced in young durian orchards to generate income while waiting for durian trees to reach maturity. Groundnut, being a short-duration legume with nitrogen-fixing ability, is commonly paired with corn in such systems. This study was carried out to evaluate the effect of different intercropping arrangements on groundnut yield and dry matter distribution. The field trial was conducted at the Faculty of Sustainable Agriculture, Universiti Malaysia Sabah, using a Randomized Complete Block Design (RCBD) with four treatments: monoculture of sweet corn (T1), monoculture of groundnut (T2), mixed relay intercropping with groundnut planted two weeks before corn (T3), and mixed relay intercropping with groundnut planted three weeks before corn (T4). Only treatments T2, T3, and T4 were considered for analysis of groundnut performance. Results showed that monoculture groundnut (T2) gave significantly higher yield in terms of both fresh and dry weight of marketable pods and seeds compared to the intercropping treatments. The lower yield in T3 and T4 was mainly due to shading from the corn canopy, which reduced light availability to the groundnut plants. While the findings indicate that groundnut performs better as a monocrop, this should be seen as a component-level result. In practice, intercropping with corn in durian orchards may still provide farmers with overall benefits through early cash income, efficient use of land, and soil fertility improvement, even though groundnut yield is reduced.